2009
DOI: 10.1021/nl9005657
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Strain-Induced Local Conductance Modulations in Single-Layer Graphene on SiO2

Abstract: Graphene has emerged as an electronic material that is promising for device applications and for studying two-dimensional electron gases with relativistic dispersion near two Dirac points. Nonetheless, deviations from Dirac-like spectroscopy have been widely reported with varying interpretations. Here we show evidence for strain-induced spatial modulations in the local conductance of single-layer graphene on SiO(2) substrates from scanning tunneling microscopic (STM) studies. We find that strained graphene exh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
124
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(128 citation statements)
references
References 30 publications
4
124
0
Order By: Relevance
“…The ability to monitor and control strain in graphene could be crucial during device fabrication, as it affects the electronic properties of the material itself [97]. For example, it has been recently shown that modulation in electrical [98] and optical [99] conductance can be induced by strain. It has been suggested that by properly modulating strain locally in graphene may lead to a controlled tuning of the electronic band gap [100].…”
Section: Discussionmentioning
confidence: 99%
“…The ability to monitor and control strain in graphene could be crucial during device fabrication, as it affects the electronic properties of the material itself [97]. For example, it has been recently shown that modulation in electrical [98] and optical [99] conductance can be induced by strain. It has been suggested that by properly modulating strain locally in graphene may lead to a controlled tuning of the electronic band gap [100].…”
Section: Discussionmentioning
confidence: 99%
“…The tension can be generated either by the electrostatic force of the underlying gate [20,21], by interaction of graphene with the side walls [22], or as a result of thermal expansion [23,24]. Our main results are as follows.…”
mentioning
confidence: 93%
“…15 Furthermore, it has been shown experimentally that graphene's electronic properties can be modified by application of an electric field 16 or mechanical strain. [17][18][19] Current applications of graphene include field-effect transistors (FETs), 20 impermeable membranes used to trap gases, 21 ultrafast photodetectors, 22 and nanomechanical resonators. 23 Besides these exceptional electronic properties, however, graphene cannot intrinsically exhibit piezoelectric properties because it belongs to a centrosymmetric point group (6/mmm or D 6h ).…”
Section: Introductionmentioning
confidence: 99%